Understanding how marketers promotes healthy organic food on Instagram non-sponsored posts - Yip, Kwan Fu (2020)
This paper aims to explore how the benefit of healthy organic food is portrayed in the brand’s non-sponsored Instagram advertisements. This study chooses Instagram Advertisements from Cascadia Farm and Nature’s Path Organic to conduct a semiotic analysis. Both companies sell organic cereal, granola, oatmeal products. They are managed in two different ways; Cascadian Farm is owned by General mill while Nature’s Path Organic is family-owned. Organic food product has become more popular over the last few years. The study tries to fill the gap of organic food advertisements as most studies focus on consumer’s attitudes and purchase intentions. This study attempts to find out how the advertisement is constructed so that it conveys the benefit of organic food products to consumers. Three advertisement are analysed from each company using the method from Zakia and Nadin (1987) literature on applied semiotics. Findings from the study show that egoistic and biospheric factors like environment, happiness, tastes, and health are most prominent in communicating the benefits of organic food products. The study also found that the advertisement uses visual and textual cues that highlight the benefits of organic food products. The advertisements use techniques such as sensory advertisements or positive message framing to promote organic food products. While both companies share themes like convenience, health aspects, and the taste of the product in their advertisement, their approach to advertising is very different. Cascadian farm promotes the product with altruistic benefit of and Nature’s Path Organic promotes the product with the biospheric benefit.